2015
DOI: 10.4049/jimmunol.1500592
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin-like Modifier FAT10 Is Selectively Expressed in Medullary Thymic Epithelial Cells and Modifies T Cell Selection

Abstract: HLA-F adjacent transcript 10 (FAT10) is a cytokine-inducible ubiquitin-like modifier that is highly expressed in the thymus and directly targets FAT10-conjugated proteins for degradation by the proteasome. High expression of FAT10 in the mouse thymus could be assigned to strongly autoimmune regulator–expressing, mature medullary thymic epithelial cells, which play a pivotal role in negative selection of T cells. Also in the human thymus, FAT10 is localized in the medulla but not the cortex. TCR Vβ-segment scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…In addition, FAT10 functions in the intracellular defense against bacteria by decorating cytoplasmic Salmonella Typhimurium that has been targeted for xenophagy 37 . Furthermore, FAT10-deficient mice are more sensitive to endotoxin challenge 38 , and FAT10 deletion in rats negatively affects virus-triggered autoimmune diabetes 39 , suggesting potential regulatory role of FAT10 during infection. The present study is the first to demonstrate this previously unreported function of FAT10 in an antiviral response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FAT10 functions in the intracellular defense against bacteria by decorating cytoplasmic Salmonella Typhimurium that has been targeted for xenophagy 37 . Furthermore, FAT10-deficient mice are more sensitive to endotoxin challenge 38 , and FAT10 deletion in rats negatively affects virus-triggered autoimmune diabetes 39 , suggesting potential regulatory role of FAT10 during infection. The present study is the first to demonstrate this previously unreported function of FAT10 in an antiviral response.…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of FAT10 in the thymus could be allocated to medullary thymic epithelial cells (mTECs) and it was shown that FAT10 modifies thymic T-cell selection, probably due to an altered peptide presentation on MHC class I molecules (Buerger et al, 2015). Additional data point to a role of FAT10 in MHC class I antigen presentation.…”
Section: Fat10 In Adaptive and Innate Immunitymentioning
confidence: 97%
“…Of all these ULMs, FAT10 is the only modifier which acts as an autonomous transferable signal for degradation by the 26S proteasome and it was shown that this process can occur independently of ubiquitin (Hipp et al, 2005;Schmidtke et al, 2009). FAT10 is a protein of the immune system and it is strongly up-regulated by pro-inflammatory cytokines (Fan et al, 1996;Raasi et al, 1999) and during the maturation of antigen presenting cells (Buerger et al, 2015;Ebstein et al, 2009;Lukasiak et al, 2008). Moreover, numerous recent publications point to a direct involvement of FAT10 in cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently published another interaction partner of AIPL1, human leukocyte antigen (HLA)-F adjacent transcript 10 (FAT10) protein (21). FAT10 belongs to the family of ubiquitin-like modifiers and is, in contrast to the ubiquitously expressed ubiquitin, constitutively expressed only in organs and unique cell types of the immune system (22)(23)(24)(25). In other cell types, FAT10 is expressed upon synergistic induction by the pro-inflammatory cytokines tumor necrosis factor (TNF)-α and interferon (IFN)-γ (26,27).…”
Section: Introductionmentioning
confidence: 99%